The Concept of Islamic Education According to Imam Al-Ghazali and Its Relevance to Contemporary Education: A Literature Analysis Study - Mohammad Nasrun (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
This literature analysis study examines the educational philosophy of Imam Al-Ghazali, a prominent Islamic scholar, and its relevance to contemporary education. The study explores Al-Ghazali's core principles of Islamic education, including the integration of religious and secular knowledge, the importance of moral and spiritual development, and the cultivation of critical thinking. The methodology involves a comprehensive review of Al-Ghazali's works, particularly his seminal work, "Ihya Ulum al-Din" (The Revival of Religious Sciences), and a synthesis of relevant scholarly literature. The findings highlight Al-Ghazali's emphasis on holistic education, which encompasses intellectual, spiritual, and practical dimensions. The study also analyzes the challenges and opportunities in applying Al-Ghazali's ideas to contemporary educational settings, such as addressing the secularization of education, promoting ethical leadership, and fostering interfaith dialogue. The conclusion emphasizes the enduring significance of Al-Ghazali's educational philosophy for shaping well-rounded individuals and contributing to a more just and equitable society. This study aims to bridge the gap between classical Islamic thought and modern educational practices, offering insights for educators, policymakers, and researchers interested in Islamic education and its role in the 21st century.